24 to Ramajay - Joseph, Terry (Express)
Only one steelband has been able to field two ensembles in this year's Pan Ramajay competition. Courts Laventille Sounds Specialists is entering both their Power House group and an ensemble called the Classic Connection in the preliminaries.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago